EFISIENSI TEKNIS USAHATANI PADI SAWAH ORGANIK DI KABUPATEN BANYUMAS - Kusmantoro Edy Sularso; Agus Sutanto (Jurnal Agribisnis Indonesia, 2020)
The research objectives are to 1) determine the role of organic fertilizers, vegetable pesticides, seeds and labour on the productivity of organic rice farming; 2) factors that cause inefficiencies in the use of production inputs in organic rice farming in Banyumas Regency. The research method used was survey method, the method of determining respondents in a purposive manner (38 farmers). The analytical method uses the stochastic frontier production function analysis method. The results showed that technically the increased use of seeds, manure, liquid organic fertilizer (POC), liquid organic KCl fertilizer and nutrition could increase the productivity of organic lowland rice in Banyumas Regency. Labor has a significant and negative effect on the productivity of organic rice farming. While pesticides have no significant effect on increasing the productivity of organic lowland rice. Management factors that influence the technical inefficiency of organic rice farming according to the signs of hope are formal education and dummy membership in farmer groups. While age and experience did not significantly affect technical inefficiency. The coefficient value of the educational variable is -0,3329 and has a significant effect on the technical inefficiency of organic rice farming. The negative sign of the formal education variable indicates that the higher the farmer's formal education level, the lower the technical inefficiency or the higher the farm's technical efficiency.